Capacity effectiveness of multihop cellular based aggregation network model - TU Lai; WANG Fu-rong; ZHANG Jian; ZHANG Fan (Tongxin xuebao)
A multihop cellular based aggregation network model was proposed, and based on network capacity region model, the capacity effectiveness of this model was analyzed. Comparison was made by both analysis and numeric simu- lation among the capacity regions and unified capacities of three network models: traditional single-hop cellular network, multihop cellular network and aggregation supported multihop cellular. Results show that the aggregation network can improve the capacity of a network even without the help of multicast and multiradio, which proves the rationality of the structure of aggregation network model.